2019
DOI: 10.1101/572313
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct Narrow and Broadband Gamma Responses in Human Visual Cortex

Abstract: High frequency activity (> 30 Hz) in the neocortical local field potential, typically referred to as the 'gamma' range, is thought to have a critical role in visual perception and cognition more broadly. Historically, animal studies recording from visual cortex documented clear narrowband gamma oscillations (NBG; ~20-60 Hz) in response to visual stimuli. However, invasive measurements from human neocortex have highlighted a different broadband or 'high' gamma response (BBG; ~70-150+ Hz). Growing evidence sugg… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Whether and how narrowband and broadband gamma are related still remains an open question (Lachaux et al, ). Broadband gamma is often observed in invasive measurements (e.g., Bartoli et al, ; Cervenka et al, ; Crone et al, ; Crone, Sinai, & Korzeniewska, ; Edwards, Soltani, Deouell, Berger, & Knight, ; Hermes et al, ) but rarely in noninvasive ones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether and how narrowband and broadband gamma are related still remains an open question (Lachaux et al, ). Broadband gamma is often observed in invasive measurements (e.g., Bartoli et al, ; Cervenka et al, ; Crone et al, ; Crone, Sinai, & Korzeniewska, ; Edwards, Soltani, Deouell, Berger, & Knight, ; Hermes et al, ) but rarely in noninvasive ones.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation why narrowband, but not broadband, gamma would be well visible in noninvasive recordings is that narrowband gamma may be spatially more coherent than broadband gamma. However, a recent study by Bartoli et al (2019) showed that the sources of narrowband gamma responses to gratings are quite focal. They examined the narrowband gamma responses with high-density ECoG grids in the visual cortex and found that the grating stimulus elicited strong narrowband gamma response across electrodes; however, the phase correlation between the electrode responses decayed fast with an estimated spatial decay constant of 2.3-2.5 mm.…”
Section: Narrowband Versus Broadband Gammamentioning
confidence: 99%
“…Broadband gamma is often observed in invasive measurements (e.g. Crone et al, 2001;Edwards et al, 2005;Crone et al, 2006;Cervenka et al, 2013;Hermes et al, 2014;Bartoli et al, 2019) but rarely in noninvasive ones.…”
Section: Narrow-vs Broadband Gammamentioning
confidence: 99%
“…The copyright holder for this preprint (which this version posted June 6, 2020. ; https://doi.org/10.1101/2020.06.05.136374 doi: bioRxiv preprint 21 baseline between and 350 Hz, a fast increasing flank peaking around 200 msec, and a slowly decreasing flank in early visual cortex (Burke et al 2014;Golan et al 2016Golan et al , 2017Gerber et al 2017;Helfrich et al 2018;Bartoli et al 2019). The high similarity of the HFA response across subjects indicates that MEG in contrast to EEG can reliably pick up high frequency activity responses to visual stimuli which even has been shown at the single trial level (Westner et al 2018).…”
Section: Discussionmentioning
confidence: 98%